A Comprehensive Study of the Importance of Materials for Renewable Energy Generation - Pranto, Jubaer Akon; Kadir, Md Moin; Khan, Md. Yakub Ali (Peneliti Teknologi Teknik Indonesia, 2024)
The main objective of this review is to show the importance of materials in renewable energy generation. Making the switch to renewable energy sources is essential for promoting sustainable growth and halting global warming. This extensive study looks at the critical role that materials play in the production of renewable energy, emphasizing how important they are for improving efficiency, cutting costs, and guaranteeing the longevity of energy systems. Key components of solar, wind, hydro, and biomass energy technologies are the subject of this study. Examples of these components are silicon for solar cells, rare earth metals for wind turbines, and organic matter for biomass conversion. It also examines the effects of cutting-edge energy storage technologies, such as supercapacitors and lithium-ion batteries, on the stability and dependability of renewable energy systems. Materials play a key role in increasing the performance and lowering the cost of renewable energy generation technologies, including fuel cells, wind turbines, solar panels, and batteries. Due to its high energy conversion efficiency and widespread availability, silicon continues to be the most widely used material in photovoltaic (PV) solar panels. However, novel materials such as perovskites offer promise for obtaining higher efficiencies at reduced manufacturing costs. The difficulties in extracting, processing, and recycling materials are discussed, highlighting the necessity of sustainable methods and creative approaches in the field of material science. Many high-performance materials are costly or challenging to manufacture on a large scale, such as advanced composites and some rare earth elements. A big problem is cutting prices and locating more plentiful alternatives. The study highlights the vital need for ongoing research and development in materials to optimize renewable energy technologies and support the worldwide move towards a low-carbon future by examining existing advancements and future potential.